Applying farmer's lenses: Two illustrations. Issue 1 (1st March 2016) - Barth, Tom
Abstract : This article reflects on how Farmer's writing on the use of multiple lenses informs two writing projects, one on values-based decision making and the other on lessons from intensive community engagement activities. Farmer's use of the business, ethical, critical theory and feminist lenses are found to be particularly relevant and useful to these writing projects, providing a deeper understanding of organizational theory and practice than reliance on any single lens.